Mapping the diachronic changes of stocking rates in a Mediterranean rural area of North Greece - Papadopoulou A.; Chouvardas D.; Abraham E. (Ecosystem services and socio-economic benefits of Mediterranean grasslands, 2016)
Livestock husbandry has rapidly changed over the last 50 years in the Mediterranean region. The main changes are the continuous processes of (i) land abandonment in the less accessible areas at a high altitude, and (ii) population transfer to more favourable areas, mainly plains. The study of the temporal spatial evolution of stocking rates is a useful tool for monitoring and analyses of sustainable rangelands management. This tool was used in the 32 Municipal Districts (MDs) of Lagadas Municipality for a period of fifty years (1961-2011). Inventory data were collected for the study area and GIS software (ArcGIS) techniques were implemented in order to produce temporal maps and tables of stocking rates (1961, 1971, 1991, 2001 and 2011). The general stocking rate decreased since 1961 in the study area. However, at low elevation, stocking rate remained higher (characterised as extreme overgrazed) than in zones of intermediate and high elevation. Interestingly the stocking rate was correlated to both proximity of settlements and population status. What is a necessity for the study area is the development of a medium and long term sustainable management plan for grazing which will deal with the issue of livestock distribution which will be developed under a serious public consultation. This consultation can ensure the involvement of the local society to the plan’s local adaptation and implementation in a long term basis.
15. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM International Network for the Research and Development of Pastures and Fodder Crops, 2016/04/12-14, Orestiada (Greece)